Discovering a new part of the phenotypic spectrum of Coffin-Siris syndrome in a fetal cohort - van der Sluijs, Pleuntje J.; Joosten, Marieke; Alby, Caroline; Attié-Bitach, Tania; Gilmore, Kelly; Dubourg, Christele; Fradin, Mélanie; Wang, Tianyun; Kurtz-Nelson, Evangeline C.; Ahlers, Kaitlyn P.; Arts, Peer; Barnett, Christopher P.; et al. (Genetics in Medicine, 2022)
Purpose: Genome-wide sequencing is increasingly being performed during pregnancy to identify the genetic cause of congenital anomalies. The interpretation of prenatally identified variants can be challenging and is hampered by our often limited knowledge of prenatal phenotypes. To better delineate the prenatal phenotype of Coffin-Siris syndrome (CSS), we collected clinical data from patients with a prenatal phenotype and a pathogenic variant in one of the CSS-associated genes. Methods: Clinical data was collected through an extensive web-based survey. Results: We included 44 patients with a variant in a CSS-associated gene and a prenatal phenotype; 9 of these patients have been reported before. Prenatal anomalies that were frequently observed in our cohort include hydrocephalus, agenesis of the corpus callosum, hypoplastic left heart syndrome, persistent left vena cava, diaphragmatic hernia, renal agenesis, and intrauterine growth restriction. Anal anomalies were frequently identified after birth in patients with ARID1A variants (6/14, 43%). Interestingly, pathogenic ARID1A variants were much more frequently identified in the current prenatal cohort (16/44, 36%) than in postnatal CSS cohorts (5%-9%). Conclusion: Our data shed new light on the prenatal phenotype of patients with pathogenic variants in CSS genes.
CRIS-Team Scopus Importer:2022-06-03
Keywords: ARID1A; ARID1B BAFopathy; BAF-complex; Fetal; SMARCA4; SMARCB1